From Jumping Gene to Cancer: Revisiting the Role of JTB Protein - Taniya M. Jayaweera; Madhuri Jayathirtha; Krishan Weraduwage; Petra Kraus; Costel C. Darie; Anca-Narcisa Neagu (Biomedicines, 2025)
Jumping translocations (JTs) are rare chromosomal abnormalities that play a crucial role in the pathogenesis of various cancer types. These rearrangements, especially those involving chromosome 1q, are frequently associated with tumor progression, therapeutic resistance, and poor prognosis. One gene of particular interest, human Jumping Translocation Breakpoint (JTB), has been identified at the site of translocation breakpoints and exhibits complex, context-dependent roles in cancer biology. JTB protein functions as a pivotal regulator in mitosis, chromosomal segregation, apoptosis, and cellular metabolism. It is functionally linked with the chromosomal passenger complex (CPC) and is implicated in processes such as epithelial–mesenchymal transition (EMT), immune evasion, and therapy resistance, especially in breast and prostate cancers. Advances in genomic, transcriptomic, and proteomic research have highlighted the significant potential of JTB as a diagnostic biomarker and a target for therapeutic interventions. This review underscores the dual role of JTB as both a tumor suppressor and oncogene, depending on the cellular context, and advocates for its continued investigation at the genomic, transcriptomic, and proteomic levels. Understanding JTB’s multifaceted contributions to tumor biology may pave the way for novel biomarkers and targeted treatments in cancer management.